Crithmum maritimum L.: Phytochemical Profile, Biological Activities, and Therapeutic Potential - Velina Dzhoglova; Stanislava Ivanova; Michaela Shishmanova-Doseva; Kremena Saracheva (Molecules, 2025)
Members of the Apiaceae family have been recognized since antiquity for their health-promoting properties. The halophytic species Crithmum maritimum L. (commonly known as sea fennel) has been used in traditional medicine since antiquity, largely due to its diverse and bioactive phytochemical composition. The plant’s complex chemical composition includes terpenoids, phenolic acids, flavonoids, tannins, dietary fibers, fatty acids, and essential vitamins. Essential oils (EOs) extracted from C. maritimum L. have demonstrated a wide range of biological activities, including antibacterial, antifungal, anti-inflammatory, antioxidant, and anticancer effects. Moreover, recent evidence suggests additional biofunctional roles such as cognitive enhancement and the inhibition of melanin synthesis in the skin. Extracts of the plant exhibit significant bioactivity, having shown antiparasitic, hypoglycemic, vasodilatory, and probiotic effects in preliminary studies. Despite this pharmacological potential, the number of experimental studies (particularly in vivo investigations) remains limited. The present review consolidates existing in vitro and in vivo research on C. maritimum L. with an analysis of 79 scientific studies aimed at elucidating its therapeutic potential and identifying future research directions necessary to support its broader application in biomedical and functional food contexts.